Uncovering adaptive mechanisms and resilience among older adults: A qualitative study on the mental health impacts of temperature variations - Jerick B. Tabudlo; Gerardo F. Joven; Marjorie F. Joven (Belitung Raya Foundation, Indonesia, 2022)
Background: Variable environmental temperature changes have affected different population groups; however, limited empirical studies in nursing have focused on older adults. One of the most pressing issues of today is climate change, where nurses should explore and advance their roles. Objective: This study aimed to explore and describe the experience of older adults with temperature variations as a consequence of climate change and its impact on mental health. Methods: Descriptive phenomenological approach was used in this study. Purposeful sampling was used in selecting key informants, while individual telephone interviews and videoconferencing platforms using a semi-structured interview guide were used as the data gathering method to gather key informants’ accounts of their experiences. Prior to data collection, authors bracket their preconceived beliefs and values regarding the phenomenon at hand. Colaizzi’s seven-step method of data analysis combined with the use of qualitative data analysis software was used to develop the themes and sub-themes. Results: Eleven key informants aged 60-77 participated in this study. Sixty significant statements on temperature variations and mental health were extracted, while forty-one meanings were formulated from the significant statements. Important meanings were grouped into a cluster of themes which built the three major themes and seven sub-themes. The major themes are Theme 1: Active recollection and recognition of their experience; Theme 2: Symptoms of physical, social, mental, and cognitive aspects transformation; and Theme 3: Establishing adaptive mechanisms. The themes reflect a mental or cognitive process of recognizing and understanding their experiences, experiencing their impacts, developing adaptive mechanisms, and showing characteristics of resilience. Conclusion: The themes and sub-themes developed in this study showed that despite their vulnerability, older adults were able to implement adaptive mechanisms and showed signs of resiliency. Temperature variations brought limitations or adjustments to the physical, social, mental, and cognitive aspects of the key informants. Further studies should be conducted in other population groups and various geographical locations to identify sources of adaptive mechanisms and resilience to temperature variations and climate change among older adults. The findings should be used in developing health programs and crafting policies.